2012
DOI: 10.1590/s0102-311x2012000200002
|View full text |Cite
|
Sign up to set email alerts
|

Contributions from the systematic review of economic evaluations: the case of childhood hepatitis A vaccination in Brazil

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
5
0
2
Order By: Relevance
“…), and the amounts used in outpatient, inpatient and transplant cases and in post-transplantation follow-up. 12 Our study has several limitations. Although we analyzed all the patients who received transplants due to ALF and who were being followed up at our center during the period studied, the sample size was small.…”
Section: Discussionmentioning
confidence: 91%
“…), and the amounts used in outpatient, inpatient and transplant cases and in post-transplantation follow-up. 12 Our study has several limitations. Although we analyzed all the patients who received transplants due to ALF and who were being followed up at our center during the period studied, the sample size was small.…”
Section: Discussionmentioning
confidence: 91%
“…It should be noted that cost-effectiveness studies need to be conducted using locally available epidemiological data as such data from other settings have low transferability 13 . Although the age-specific incidence of hepatitis A infection had a significant impact on cost-effectiveness finding 12 , we found that many included studies 20 , 21 , 27 , 28 , 31 adopted such data from the US study 54 , 55 , 71 .…”
Section: Discussionmentioning
confidence: 99%
“…The most comprehensive study 12 published in 2018 included four studies from MICs and 27 studies from HICs. Another systematic review included nine studies conducted in MICs, which were published till 2012 13 . The other identified 11 EE studies, were published between 1995 and 2010 14 .…”
mentioning
confidence: 99%
“…Embora continue sendo bastante notificada no Brasil 11 , a hepatite A é uma doença prevenível através da vacina, que é altamente eficaz. A vacina contra a hepatite A apresenta custo-efetividade no Brasil positivo ao se considerar o custo da vacina, a incidência da doença e os custos gastos com os serviços médicos-hospitalares 12 . Desta forma, com a implementação desta vacina no Programa Nacional de Imunização no Brasil no ano de 2014, mesmo ano dos dados do presente estudo, espera-se que a prevalência de vacinados aumente e, em consequência, reduzam-se as notificações de novos casos.…”
Section: Artigo Originalunclassified